2017
DOI: 10.1123/jpah.2016-0529
|View full text |Cite
|
Sign up to set email alerts
|

Greater Adherence to Recommended Morning Physical Activity is Associated With Greater Total Intervention-Related Physical Activity Changes in Bariatric Surgery Patients

Abstract: Background This study examines whether performance of bout-related physical activity (PA) during morning hours is related to greater overall bout-related PA increases within a preoperative PA intervention for bariatric surgery (BS) patients. Methods Participants with severe obesity (n = 33; mean age = 45.6 ± 9.6 years; BMI = 45.7 ± 7.0 kg/m2) seeking BS were randomized to and completed 6 weeks of preoperative PA counseling (retention = 82.5%). Participants were encouraged to walk daily at a moderate intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
(23 reference statements)
0
11
1
Order By: Relevance
“…Among those who reported a temporally consistent PA routine, early morning was the most common time that exercise was performed, followed by evening. In contrast with our hypothesis and previous work , the particular time of day at which temporally consistent exercisers most often performed PA was not differentially related to PA levels. Our findings thus add to the mixed literature on the optimal time of day, if any, for PA. Because all temporally consistent exercisers in the present study reported, by definition, exercising at the same time day to day, it is likely that these individuals had well‐established PA routines.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Among those who reported a temporally consistent PA routine, early morning was the most common time that exercise was performed, followed by evening. In contrast with our hypothesis and previous work , the particular time of day at which temporally consistent exercisers most often performed PA was not differentially related to PA levels. Our findings thus add to the mixed literature on the optimal time of day, if any, for PA. Because all temporally consistent exercisers in the present study reported, by definition, exercising at the same time day to day, it is likely that these individuals had well‐established PA routines.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings thus add to the mixed literature on the optimal time of day, if any, for PA. Because all temporally consistent exercisers in the present study reported, by definition, exercising at the same time day to day, it is likely that these individuals had well‐established PA routines. Perhaps among individuals who have already established a strong PA habit, the particular time of day at which PA is performed is less important than overall temporal consistency in PA. As indicated by prior research, however, morning PA performance may be especially important for initially developing a PA habit and for PA adoption . The finding that nearly half of temporally consistent exercisers were early‐morning exercisers also suggests that performing PA in the early morning may be helpful for maintaining a regular PA routine, although these individuals were not more active than their counterparts in the present study and we cannot determine causality from the present data.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations